Molecular docking utilising the OliveNet™ library reveals novel phenolic compounds which may potentially target key proteins associated with major depressive disorder. (June 2020) - Pitsillou, Eleni; Liang, Julia; Hung, Andrew; Karagiannis, Tom C.
Graphical abstract: Highlights: The phenolic compounds (222) from OliveNet TM were screened for their ability to target proteins implicated in depression. Novel candidate phenolics for monoamine oxidase A (MAO-A) were hydroxytyrosol-4-β-glucoside and salidroside. Hydroxytyrosol rhamnoside and a derivative of oleuropeindial were shown to bind with relatively high affinity to MAO-B. Several relatively more well-known phenolics were shown to bind to pharmacological targets beyond the MAO enzymes. The lead compounds could be purified or synthesised for further validation and experimentation. Abstract: The antidepressant medications that are currently prescribed to patients suffering from major depressive disorder (MDD) have limitations and as a result, there is an urgent need to increase the options that are available. A number of studies have found that natural polyphenols have neuroprotective properties and there is evidence to suggest that they modulate neurotransmitter systems. There are more than 200 phenolic compounds that have been identified in Olea europaea, many of which have not yet been investigated for their potential biological effects. In this study, in silico methods were used to screen the phenolic library from the OliveNet™ database and identify novel lead compounds for proteins implicated in the pathophysiology of MDD. The molecular docking results revealed that the monoamine oxidase enzyme isoforms (MAO-A/MAO-B) had binding specificities for certain phenolic subclasses. The lead ligands that were identified from these subclasses were positioned near the flavin adenine dinucleotide (FAD) cofactor, interacting in a similar manner as known inhibitors. In addition to the MAO enzymes, several phenolic compounds were docked to neurotransmitter transporters and postsynaptic receptors, as well as proteins involved in neuroinflammation, oxidative stress and the endocannabinoid system. Based on the binding affinity, position, orientation and interactions of the lead phenolic compounds identified in this study, it is predicted that they may have antidepressant properties. The results should be validated further using molecular dynamics (MD) simulations, as well as in vivo and in vitro techniques.